Analysis of The Influence of Promotion Through Digital Marketing and Effectiveness of Marketing Communication on Customer Decisions in Hospitality Industry - Irwansyah Rezeki, Syailendra Reza; Dharmawan, Donny; Azlina, Yunidyawati; Purwanti; Kespandiar, Tengku (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to determine the marketing communication strategies used to increase occupancy. We used qualitative and descriptive research. The researcher employed a case study as the research method. In-depth interviews provided the techniques for collection. The research results revealed that the public relations division, in collaboration with the hotel marketing team, designed and implemented the marketing communication strategy. Public relations is a communication facilitator, especially in communicating hotel products and services through various marketing strategies. This strategy is divided into three, namely the push strategy, which uses distributors or travel agents to encourage customers to use hotel products; the pull strategy, which uses advertising, sales promotions, personal sales, and direct marketing to attract customer interest in hotel products and services, also the profile strategy, which uses public relations to build the hotel's image and reputation to increase customer trust and sales. This research suggests that further research be carried out in quantitative form to obtain a more detailed understanding of the success of each factor that influences marketing communication strategies, such as push, pull, and profile strategies. Meanwhile, from a practical perspective, conducting a more detailed evaluation of each marketing communication tool used by measuring its effectiveness to select the most effective tools in increasing sales or occupancy is recommended.